Pengaruh Audit Fee, Opini Going Concern, Financial Distress, Ukuran Perusahaan Klien, Kepemilikan Institusional, Dan Kompleksitas Perusahaan Terhadap Auditor Switching(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2015) - Handini, Ulfi Yulia Mutiara; , Drs. Suyatmin Waskito Adi, M.Si (2017)
Auditor switching is a changes of auditor performed by the client company. The purpose of this research was to etermine the effect of audit fee, going concern opinion, financial distress, the clients size, institutional ownership, and the company complexity toward auditor switching on manufacturing companies listed in Indonesia Stock Exchange. The analitical method applied in this research was the logistic regression. The population in this research is the manufacturing companies listed in Indonesia Stock Exchange 2011-2015. Samples were selected by the purposive sampling, the obtained samples were 100 companies. The results, showed that the audit fee, the going concern opinion, financial distress, institutional ownership, and the company complexity had no effect toward auditor switching. However the variable client size to proved that there is an effect toward auditor switching.